(untitled) (Boca Raton,Pensacola, FL, 2007)
This book covers the techniques and approaches for assessing suspected contaminant impact upon freshwater bivalves. The editors meet this challenge by incorporating expertise on research topics and management issues from a cross section of active scientists in the field. The resulting array of viewpoints provides a valuable tool drawn from both internal and external peer reviews. They explore current advances in general monitoring of population responses to stressors, fundamental concepts of ecotoxicology specific to burrowing bivalves, and useful insights that offer direction and priority for resolving specific problems challenging protection and conservation efforts
Keywords: Freshwater mussels,Indicators (Biology),Water quality bioassay,Phân tích chất lượng nước; Effect of water pollution on